2014
DOI: 10.1016/j.jval.2014.08.357
|View full text |Cite
|
Sign up to set email alerts
|

Incidence-Based Cost of Asthma in Vietnam

Abstract: Objectives: To analyze the risk factors associated with the out-come of hospital acquired pneumonia (HAP). MethOds: A prospective observational study, carried out in a tertiary care teaching hospital. HAP patients who fulfill the inclusion criteria were identified and enrolled into the study after taking informed consent. Patients were followed from the day of diagnosis of HAP to till the day of discharge/death. The patient data like demography, social habits, co-morbid diseases, interventions (mechanical vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“… 9 Many reasons exist for this low level of asthma control, for example, related to the health care system and/or the doctor–patient relationship. Besides issues related to the health care system (e.g., unavailability of controllers, 10 unaffordability for some patients 1 , 2 , 11 – 13 ) or to physicians (e.g., incorrect diagnosis, lack of knowledge on asthma management, insufficient time or unwillingness to discuss matters with patients) 14 , 15 and patient-related problems (e.g., low level of treatment adherence), the patient’s low level of knowledge about the disease (particularly knowledge on self-management) is an important factor contributing to the low level of asthma control. 16 …”
Section: Introductionmentioning
confidence: 99%
“… 9 Many reasons exist for this low level of asthma control, for example, related to the health care system and/or the doctor–patient relationship. Besides issues related to the health care system (e.g., unavailability of controllers, 10 unaffordability for some patients 1 , 2 , 11 – 13 ) or to physicians (e.g., incorrect diagnosis, lack of knowledge on asthma management, insufficient time or unwillingness to discuss matters with patients) 14 , 15 and patient-related problems (e.g., low level of treatment adherence), the patient’s low level of knowledge about the disease (particularly knowledge on self-management) is an important factor contributing to the low level of asthma control. 16 …”
Section: Introductionmentioning
confidence: 99%
“…The majority of the ambulatory care of asthma in Vietnam is provided by primary care physicians (PCPs); however, the use of controller medications (eg, inhaled corticosteroids [ICS]) in this setting is challenge because of their unavailability 11 and/or unaffordability for patients with a low/average income. 1 , 2 , 12 – 14 Apart from this, lack of knowledge on asthma management by health care providers is another factor contributed to this low level of asthma control. It has been shown that knowledge and competence of PCPs are low and vary among countries and with time in the same country, 15 – 19 but these could be improved by education.…”
Section: Introductionmentioning
confidence: 99%
“…Tại thành phố Hồ Chí Minh, tỷ lệ trẻ em từ 6-7 tuổi từng bị HPQ là 10,9%, cao nhất ở khu vực châu Á -Thái Bình Dương [5]. Theo ước tính, tất cả các chi phí trực tiếp và gián tiếp đề điều trị cho một ca bệnh HPQ mới tại Việt Nam khoảng 70 triệu đồng [80], kinh tế Việt Nam phải chịu liên quan đến bệnh HPQ lên đến 16.193 tỷ đồng mỗi năm [8].…”
Section: đặT Vấn đềunclassified